FORMATION OF THE MODEL OF THE QUALITY MANAGEMENT PROCESS OF SERVICES OF ELECTRIC DISTRIBUTION ENTERPRISES IN THE CONDITIONS OF TRANSFORMATION OF THE ENERGY MARKET OF UKRAINE - Stankovska, I. M.; Stankovskyi Т. V.; Shaban, L.R. (The actual problems of regional economy development, 2019)
The article investigates the problems associated with the formation of a model of quality management process for services of electricity distribution companies in the conditions of transformation of the Ukrainian energy market. The purpose of the study is to identify ways toimprove the quality of services that will enable electricity distribution companies to operate effectively in competitive conditions. The methods of theoretical generalization were used to solve the set tasks - to formulate definitions of concepts and general approaches and principles; analysis and synthesis; systematic and comprehensive analysis; statistical and graphical methods of analysis - for quantitative and qualitative reflection of existing trends. In order to achieve this goal and to ensure the efficient functioning of the electricity distribution companies, the following analyzes have been made: transformations into the Ukrainian energy market, which lead to changes in the activity of these enterprises; dynamics of electricity production and distribution by types of economic activity; the quality of services provided to electricity distribution companies and its evaluation through the SAIDI index (average duration of power outages to consumers); identified components that affect the quality of services of electricity distribution companies; priority objectives of strategic activity of electricity distribution companies have been determined; model of process of quality management of services is formed. Research has scientific novelty and practical value, which is as follows: - research of transformation processes taking place on the energy market emphasizes the attention of the monopolists-service providers, that for the efficient operation of the electricity distribution companies it is necessary to take into account the newly created competitive environment and work in the conditions of competition; - the formed model of quality management of services of electricity distribution companies gives an opportunity to distinguish the basic processes in quality management and to ensure their effective implementation; - Carrying out quality assessment of services from a stakeholder perspective in the implementation of the service will ensure the objectivity of the process and allow for further quality improvements, taking into account the needs of consumers and service providers, with mandatory compliance with quality standards.